Does the Cranial Mesenchyme Contribute to Neural Fold Elevation During Neurulation? - Zohn, Irene E. (2012)
The central nervous system is derived from the neural plate that undergoes a series of complex morphogenetic events resulting in formation of the neural tube in a process known as neurulation. The cellular behaviors driving neurulation in the cranial region involve forces generated by the neural tissue itself as well as the surrounding epithelium and mesenchyme. Of interest, the cranial mesenchyme underlying the neural plate undergoes stereotypical rearrangements hypothesized to drive elevation of the neural folds. As the neural folds rise, the hyaluronate-rich extracellular matrix greatly expands resulting in increased space between individual cranial mesenchyme cells. Based on inhibitor studies, expansion of the extracellular matrix has been implicated in driving neural fold elevation; however, since the surrounding neural and epidermal ectoderm were also affected by inhibitor exposure, these studies are inconclusive. Similarly, treatment of neurulating embryos with teratogenic doses of retinoic acid results in altered organization of the cranial mesenchyme but alterations in surrounding tissues are also observed. The strongest evidence for a critical role for the cranial mesenchyme in neural fold elevation comes from studies of genes expressed exclusively in the cranial mesenchyme that when mutated result in exencephaly associated with abnormal organization of the cranial mesenchyme. Twist is the best studied of these and is expressed in both the paraxial mesoderm and neural crest derived cranial mesenchyme. Here we review the evidence implicating the cranial mesenchyme in providing a driving force for neural fold elevation to evaluate whether there is sufficient data to support this hypothesis.